The Strandja Massif and the İstanbul Zone were once parts of the same palaeotectonic unit: new data from Triassic detrital zircons. Issue 1 (1st January 2018) - Ülgen, Semih Can; Lom, Nalan; Sunal, Gürsel; Gerdes, Axel; Şengör, Ali Mehmet Celâl
ABSTRACT: Spatially continuous rock assemblages that share similar environmental evolution or structural features can be classified as a single tectonic unit. This approach enables to link dispersed units or massifs with each other and sometimes can be subjective, depending on the classification criteria. The relationship and the nature of the contact between the Strandja Massif and the İstanbul Zone have been controversial due to the Cainozoic cover. Amalgamation of these units was claimed as early as the Aptian-Albian. Lower Triassic sedimentary rocks, which are overlain by the Carboniferous flysch with a N-verging thrust fault are exposed NW of the İstanbul Zone. This study reveals the spatial relationship between the Strandja Massif and the İstanbul Zone deduced from the U-Pb dating and Lu-Hf isotopes of the detrital zircons from these Lower Triassic clastics. Our results show that the early Triassic basin was fed from a provenance that included arc-related Upper Carboniferous-Lower Permian magmatic rocks which is much more likely to be the Strandja Massif than the İstanbul Zone. The second outcome of this study is that a unit that previously assigned to Palaeozoic turned out to be Triassic, which brings the Strandja Massif farther to the east, into the northern İstanbul Zone.